2019
DOI: 10.1101/597989
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How the Avidity of Polymerase Binding to the -35/-10 Promoter Sites Affects Gene Expression

Abstract: Although the key promoter elements necessary to drive transcription in Escherichia coli have long been understood, we still cannot predict the behavior of arbitrary novel promoters, hampering our ability to characterize the myriad of sequenced regulatory architectures as well as to design novel synthetic circuits. This work builds on a beautiful recent experiment by Urtecho et al. who measured the gene expression of over 10,000 promoters spanning all possible combinations of a small set of regulatory elements.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…In fact, conserved motifs such as the À10 and À35 region in bacteria might not have additive effects as it long was thought. Recently, Einav et al (2019) improved their computational model that predicts the behaviour of novel promoters by factoring in avidity between the À10 and À35 regions. Avidity describes how the two binding sites influence each other's binding strength.…”
Section: Host-specific Contextmentioning
confidence: 99%
“…In fact, conserved motifs such as the À10 and À35 region in bacteria might not have additive effects as it long was thought. Recently, Einav et al (2019) improved their computational model that predicts the behaviour of novel promoters by factoring in avidity between the À10 and À35 regions. Avidity describes how the two binding sites influence each other's binding strength.…”
Section: Host-specific Contextmentioning
confidence: 99%
“…In particular, we sought to learn how these sites may be manipulated to generate lacUV5 variants with minimal leakiness and maximal fold-change, properties that are generally desired in synthetic applications. In previous work, we have found that testing large libraries of promoters composed of various combinations of sequence elements allows us to characterize the contribution of individual sequence elements and reveal interactions between these elements 20,44 . We utilized our MPRA to uncover how tuning binding sites within the lacUV5 promoter affects the fold-change and leakiness of this system.…”
Section: Tuning Binding Site Strengths Alters Inducible Promoter Behamentioning
confidence: 99%
“…We designed and assayed a library of 1,600 inducible promoters, which we refer to as Pcombo, composed of all possible combinations of one of ten proximal LacI binding sites at +11, four -10 elements, four -35 elements, and ten distal LacI sites at -90 ( Figure 2A) . To cover a wide range of expression, we selected -10 and -35 element variants previously shown to span a range of RNAP binding affinities 6,20,44 . Similarly, we chose a range of LacI binding site variants from well-characterized genomic operator sites (O 1 , O 3 , O sym ) 10,18 , a variant of the natural O 2 site, O 2-var , and a series of novel LacI sites created from different combinations of the monomeric halves of each of these dimeric binding sites ( Table S2 ).…”
Section: Tuning Binding Site Strengths Alters Inducible Promoter Behamentioning
confidence: 99%
See 1 more Smart Citation
“…Gene expression regulation is being studied by many researchers whose insights improve our capacity to control and modify living systems (11)(12)(13)(14). However, we still do not fully understand how some elementary properties of the interaction of a TF with its binding site on DNA affect the stochastic dynamics of gene expression and the acquisition of information (15). One of these properties is a TF's residence time on its DNA binding site -the mean time that a TF remains bound to DNA.…”
Section: Introductionmentioning
confidence: 99%